Cultural Contextualization Of Indonesian Values In The Tafsir Al-Iklīl Fī Ma’ānī Al-Tanzīl By Misbah Musthofa (A Study Of Wilhelm Dilthey's Hermeneutics) - Adlan Maghfur, Adlan Maghfur; Lailatul Mu'jizati, Lailatul Mu'jizati; Agung Kurniawan; Nurul Ahmadi (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
This study argues that the integration of Indonesian cultural values into Qur’anic exegesis can be achieved without compromising the sacredness of the text, as demonstrated in Misbah Musthofa’s Al-Iklīl fī Ma’ānī al-Tanzīl, interpreted through Wilhelm Dilthey’s hermeneutics. The research investigates how Dilthey’s focus on historical understanding, empathy, and cultural context enables Musthofa to interpret Qur’anic verses in a way that incorporates Indonesia’s ethnic diversity, traditions, and customs. The research employs a qualitative method with hermeneutical analysis, covering textual description of the exegesis, interpretation of Indonesian cultural contexts, and evaluation of Dilthey’s principles (Erleben, Verstehen, and Auslegen). Primary data are obtained from Tafsir Al-Iklīl, while secondary data include literature on Indonesian culture and hermeneutic theory. The results show that Musthofa successfully contextualizes Indonesian culture through a holistic interpretation for instance, by connecting Qur’anic verses to social realities during the time of writing, such as his interpretation of Surah Al-Baqarah verse 10 in relation to the Javanese ritual practice of offering sesajen (traditional offerings). This approach enriches Qur’anic interpretation with local dimensions, making it more relevant for Indonesian Muslims. However, a key challenge remains in maintaining a balance between cultural context and the authoritative nature of the Qur’anic text. The study concludes that Dilthey’s hermeneutics offers an effective framework for contextualizing Qur’anic interpretation in Indonesia. It supports inclusive, adaptive readings relevant to contemporary challenges. Future research should examine other regional exegeses.